Emerging Concern for Silver Nanoparticle Resistance in Acinetobacter baumannii and Other Bacteria - McNeilly, Oliver; Mann, Riti; Hamidian, Mohammad; Gunawan, Cindy (Frontiers in Microbiology, 2021)
The misuse of antibiotics combined with a lack of newly developed ones are the main contributors to the current antibiotic resistance crisis. There is a dire need for new and alternative antibacterial options and nanotechnology could be a solution. Metal-based nanoparticles, particularly silver nanoparticles (NAg), have garnered widespread popularity due to their unique physicochemical properties and broad-spectrum antibacterial activity. Consequently, NAg has seen extensive incorporation in many types of products across the healthcare and consumer market. Despite clear evidence of the strong antibacterial efficacy of NAg, studies have raised concerns over the development of silver-resistant bacteria. Resistance to cationic silver (Ag+) has been recognised for many years, but it has recently been found that bacterial resistance to NAg is also possible. It is also understood that exposure of bacteria to toxic heavy metals like silver can induce the emergence of antibiotic resistance through the process of co-selection. Acinetobacter baumannii is a Gram-negative coccobacillus and opportunistic nosocomial bacterial pathogen. It was recently listed as the “number one” critical level priority pathogen because of the significant rise of antibiotic resistance in this species. NAg has proven bactericidal activity towards A. baumannii, even against strains that display multi-drug resistance. However, despite ample evidence of heavy metal (including silver; Ag+) resistance in this bacterium, combined with reports of heavy metal-driven co-selection of antibiotic resistance, little research has been dedicated to assessing the potential for NAg resistance development in A. baumannii. This is worrisome, as the increasingly indiscriminate use of NAg could promote the development of silver resistance in this species, like what has occurred with antibiotics.